Barcode-based filing information system in hospitals - Agung Suryadi; Imam Hizbullah; Diana Agustin Fibriyani; Febriza Rose Diagnostikasari (LPPM Universitas Duta Bangsa Surakarta, 2021)
Information technology plays a major role in the development of health care systems, one of which is in hospitals. Surakarta City’s Central General Hospital (RSUP) continues to use a traditional filing system. Several barriers remain in the way of implementing these activities, including misfile media record documents and difficulty locating medical record documents. The research method used in this study is descriptive research with data collection methods of observation and interviews. The subjects of this study were medical record officers, and the instruments used in this study were observation guidelines and free guided interview guidelines. Primary and secondary data sources were used in this study. The method of data collection and processing at the Central General Hospital (RSUP) in Surakarta City is collected through the processes of drm data input, borrower data input, borrowing data input, return data input, and evaluation data input, and is then processed quantitatively. The records from the inpatient medical record are then saved to the drm table, borrower table, loan table, return table, and assessment table, and used to produce filing information system production, borrower reports, loan reports, return reports, and appraisal reports using the PHP programming language and the Dream wevare application with a MySQL database.